2001
DOI: 10.1007/s004140000194
|View full text |Cite
|
Sign up to set email alerts
|

Markers of cardiac oxidative stress and altered morphology after intraperitoneal cocaine injection in a rat model

Abstract: This study was designed to assess the parameters of myocardial oxidative stress and related cardiac morphological changes following intraperitoneal cocaine exposure in rats. The cardiac levels of reduced glutathione(GSH), oxidised glutathione(GSSG), ascorbic acid (AA), and the production of malondialdehyde (MDA) were measured, as well as the variations of activity in the enzyme systems involved in cell antioxidant defence, glutathione peroxidase (GSH-Px), glutathione reductase (GR) and superoxide dismutase (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…Recent studies have shown that oxidation of catecholamines results in the formation of highly toxic substances such as aminochromes (e.g. adrenochrome) and free radicals and by virtue of the latter's actions on different types of heart membranes, which cause intracellular Ca 2+ overload and myocardial cell damage [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that oxidation of catecholamines results in the formation of highly toxic substances such as aminochromes (e.g. adrenochrome) and free radicals and by virtue of the latter's actions on different types of heart membranes, which cause intracellular Ca 2+ overload and myocardial cell damage [38].…”
Section: Discussionmentioning
confidence: 99%
“…HSPs fulfill a range of functions, including cytoprotection and the intracellular assembly, folding, and translocation of oligomeric proteins, and represent a rapid response to altered redox states [23,26,27]. In addition to acting as cellular chaperones, HSPs mediate cytoprotection by associating with and hindering the action of key apoptotic proteins, and by facilitating the degradation of misfolded intracellular proteins by the ubiquitin/proteasome system, so-called protein triage [23].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, chronic cocaine binging might alter signaling pathways downstream of NO production such as cyclic GMP. Finally, cocaine binging may alter nitroso-redox balance (Devi and Chan, 1996;Fineschi et al, 2001;Moritz et al, 2003aMoritz et al, , 2004Pacifici et al, 2003;Kovacic, 2005) by increasing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%